Digital competence, faculty and higher education: Bibliometrics from the Web of Science - Cisneros-Barahona, Andrés; Marqués Molías, Luis; Samaniego-Erazo, Nicolay; Uvidia-Fassler, María Isabel; Castro-Ortiz, Wilson; Villa-Yánez, Henry (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Using the Bibliometrix software package and the Prisma Guide, a bibliometric analysis of the literature from the Web of Science on university teaching digital competence was developed. Research is delimited through Eric’s thesauri. Research questions related to data sources, authors, and collaborative networks were raised. The research shows increases in production as of 2019, the nationality of the authors and the affiliation of institutions stand out through extensive research networks in Ibero-America. It is necessary to extend this study to other scientific bases.